Markers associated with genomic instability, immunogenicity and immune therapy responsiveness in Metaplastic carcinoma of the breast: Expression of γH2AX, pRPA2, P53, PD-L1 and tumor infiltrating lymphocytes in 76 cases - S. Voutilainen; P. Heikkilä; J. Bartkova; H. Nevanlinna; C. Blomqvist; J. Bartek; J. Mattson (BMC Cancer, 2022)
Abstract Background Metaplastic breast cancer (MpBC) is an aggressive subtype of breast carcinoma that is often resistant to conventional chemotherapy. Therefore, novel treatment strategies are urgently needed. Immune check point inhibitors have shown activity in programmed death-ligand 1 (PD-L1) – positive metastatic triple negative breast carcinoma (TNBC), which raises the possibility that immunotherapy may also be effective in MpBC as most of the MpBCs are triple negative. The aim of the present study was to assess genomic instability and immunogenicity in tumor specimens of patients with MpBC. Methods A total of 76 patients diagnosed with MpBC over a 15-year period were included in the study. We performed immunohistochemical analyses for tumor cell PD-L1, immune cell PD-L1 and p53 on tissue microarrays (TMAs), analyzed stromal and intratumoral tumor infiltrating lymphocytes (TILs) from hematoxylin and eosin-stained (H&E) slides and scored gamma-H2AX (γH2AX) and phosphorylated-RPA2 (pRPA2) from whole tissue sections. We correlated marker expression with clinicopathologic features and clinical outcome. Results All tumors expressed γH2AX and pRPA2 with median expressions of 43% and 44%. P53- (68%), tumor cell PD-L1- (59%) and immune cell PD-L1-positivity (62%) were common in MpBCs. Median stromal TIL and intratumoral TIL counts were 5% and 0. The spindle and squamous cell carcinomas expressed the highest levels of PD-L1 and TILs, and carcinoma with mesenchymal differentiation the lowest. Conclusions MpBC appears to be an immunogenic cancer with high genomic instability and frequent PD-L1-positivity, implying that check point inhibitors might be effective in MpBC. Expression levels of PD-L1 and TILs varied across different histologic subtypes, suggesting that immunotherapy might be less effective in carcinoma with mesenchymal differentiation.